Exception handling with Petri net for digital systems - De Oliveira, W. L.A.; Marranghello, N. [UNESP]; Damiani, F. (Institute of Electrical and Electronics Engineers (IEEE), 2002)
Petri net is a language for system modeling. Petri net extensions achieve a wide range of applications, such as: communication protocols, programming languages, computer architectures, distributed systems, industrial process control. These extensions allow the description of parallel systems, which can be simulated at the temporal, logical, and functional levels with reasonable simplicity. Such extensions have some limitations when describing digital systems. This paper presents an extension to overcome the existing limitations. Emphasis is placed on PNDS mechanisms aimed at exception handling.